Interest in Illicit Purchase of Cigarettes Under a Very Low Nicotine Content Product Standard - Hall, Marissa G (Nicotine Tob Res, 2019)
SIGNIFICANCE: The US Food and Drug Administration (FDA) is considering a very low nicotine content (VLNC) product standard to substantially reduce nicotine in cigarettes. We examined whether learning about a potential VLNC standard increased smokers’ interest in illicit purchases of cigarettes with regular nicotine content if such a standard were adopted. METHODS: Participants were a national convenience sample of 1712 US adult smokers. In an online experiment, we randomly assigned smokers to view information about a new VLNC standard (experimental condition) or no information (control condition). The experimental condition explained that a VLNC standard would remove 95% of the nicotine in cigarettes and would require stores to only sell VLNC cigarettes. Then, the survey assessed smokers’ interest in purchasing regular cigarettes from three illicit sources. RESULTS: Smokers who learned about the VLNC standard were more likely to be very or extremely interested in purchasing regular cigarettes illicitly from a Web site compared to smokers in the control group (24% vs. 16%, p < .001). They were also more interested in illicitly buying cigarettes from a street vendor (19% vs. 13%, p < .001) and a store on an Indian reservation (28% vs. 22%, p < .05), compared to the control. The impact of learning about the VLNC standard on interest in illicit purchases did not differ by smoking frequency or current e-cigarette use. CONCLUSIONS: A VLNC standard could increase smokers’ interest in illicit purchases of regular nicotine cigarettes. To prevent VLNC-induced illicit trade from undermining public health, FDA should consider proven measures such as track and trace for these products. IMPLICATIONS: Little is known about how a VLNC cigarette standard would affect consumer interest in regular content cigarettes purchased from illicit sources (eg, the Internet). We found that smokers informed about a potential VLNC product standard had greater interest in illicit cigarette purchases, compared to controls. This suggests the importance of proactive measures accompanying a VLNC standard, such as track-and-trace cigarette packaging regulations and communication campaigns, in order to maximize the standard’s public health impact.